Epithelial-mesenchymal transition-related long noncoding RNAs in gastric carcinoma - Feng, Ying-Nan; Li, Bo-Ya; Wang, Ke; Li, Xiao-Xi; Zhang, Lan; Dong, Xian-Zhe (Frontiers in Molecular Biosciences, 2022)
As an evolutionarily phenotypic conversion program, the epithelial-mesenchymal transition (EMT) has been implicated in tumour deterioration and has facilitated the metastatic ability of cancer cells via enhancing migration and invasion. Gastric cancer (GC) remains a frequently diagnosed non-skin malignancy globally. Most GC-associated mortality can be attributed to metastasis. Recent studies have shown that EMT-related long non-coding RNAs (lncRNAs) play a critical role in GC progression and GC cell motility. In addition, lncRNAs are associated with EMT-related transcription factors and signalling pathways. In the present review, we comprehensively described the EMT-inducing lncRNA molecular mechanisms and functional perspectives of EMT-inducing lncRNAs in GC progression. Taken together, the statements of this review provided a clinical implementation in identifying lncRNAs as potential therapeutic targets for advanced GC.